Implementation Of Competency Improvement Policy For Job Seekers By The North Central Timor Regency Manpower And Transmigration Office - Legan, Eugenius Yogeputra; Fritantus, Yohanes; Rembu, Yoakim (Universitas Negeri Gorontalo, 2025)
The purpose of this study is to describe how